PHENOMENON OF MAX FACTOR: MAKEUP FATHER AND HOLLYWOOD WIZARD - Zazimko , Kateryna; Gudkova , Nataliia (Collection of scientific papers «ΛΌГOΣ», 2022)
Today, the art of make-up occupies an important place in the structure of the fashion image: thematic, catwalk, festive, stage, entertainment. The meaning of the term makeup is well-known for everybody nowadays. It is a subset of cosmetics, which refers primarily to coloured products intended to alter the user’s appearance [1]. Beauty products business is huge, this is a whole empire with its own rules. This part of life is extremely important for every person, therefor there is a bunch of new beauty products and their advertising that we face every day.